Unsur Kebudayaan Jawa – Belanda dalam Novel Student Hidjo Karya Mas Marco Kartodikromo (Kajian Antropologi Sastra) - Trisfayani Trisfayani; Rafiza Rafiza; Maulidawati Maulidawati (Departement of Mathematics Education, 2023)
This research is entitled Elements of Javanese – Dutch Culture in Mas Marco Kartodikromo's Student Hidjo Novel (Literary Anthropological Studies). This study aims to describe elements of Javanese culture and elements of Dutch culture contained in the novel Student Hidjo by Mas Marco Kartodikromo. The source of data is the novel Student Hidjo by Mas Marco Kartodikromo. The approach used is the approach of literary anthropology. The method used in this study is a qualitative descriptive method. The data collection techniques used are reading, recording, and literature studies. From the results, the elements of Javanese cultural and Dutch cultural exist in this novel. In terms of data that indicating elements of Javanese culture in Student Hidjo Novel, 7 data were found related to living equipment and technology, 8 data related to livelihoods, 14 data related to the societal system, 20 data related to cultural elements related to language, 4 data related to the arts, 3 data relating to knowledge systems, 5 data related to religion. Meanwhile, elements of Dutch culture in Student Hidjo novels related to living equipment and technology were found 2 data, 6 data related to livelihoods, 2 data related to the societal system, 50 data related to language, 2 data related to art, 3 data related to the knowledge system, while no data was found related to religion. Of the seven cultural elements, all proves the difference between Javanese culture and Dutch culture in the novel Student Hidjo.